Pengujian Efektivitas Starter Jamur Beauveria Bassiana Terhadap Mortalitas Hypothenemus Hampei : Study The Efectivity Of Beauveria Bassiana Starter Toward The Mortality Of Hypothenemus Hampei - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Abstract: An experiment concerning to the production of B. bassiana starter had been conducted to facilitate its use to the farmers. The production ofstarter was conducted by using maize rice mill as the growing medium of B. bassiana. To examine the effectiveness of the starter